2021
DOI: 10.3390/brainsci11111396
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Activity and Network Connectivity to Dynamic and Static Emotional Faces in 7-Month-Old Infants

Abstract: The present study investigated whether, as in adults, 7-month-old infants’ sensorimotor brain areas are recruited in response to the observation of emotional facial expressions. Activity of the sensorimotor cortex, as indexed by µ rhythm suppression, was recorded using electroencephalography (EEG) while infants observed neutral, angry, and happy facial expressions either in a static (N = 19) or dynamic (N = 19) condition. Graph theory analysis was used to investigate to which extent neural activity was functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(154 reference statements)
1
5
0
Order By: Relevance
“…In particular, consistent with previous adult studies [ 12 , 16 ] and with Gardner and colleagues’ social monitoring model [ 3 ], we predicted that ostracized children would show heightened emotion recognition abilities as compared to included ones, anger and fear being especially relevant in socially-threatening situations such as ostracism. Alternatively, in agreement with most recent models on the development of emotion recognition abilities attributing distinct visual and neural processing in response to different emotions [ 37 39 , 51 , 52 ], it is also possible that the effects of ostracism may differ depending on the observed emotion. In line with the available literature, we expected age to modulate children’s ability to recognize emotions, with older children showing better emotion recognition performance than younger ones, but we presumed that in both age groups recognition of emotional expressions could be modulated by ostracism.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…In particular, consistent with previous adult studies [ 12 , 16 ] and with Gardner and colleagues’ social monitoring model [ 3 ], we predicted that ostracized children would show heightened emotion recognition abilities as compared to included ones, anger and fear being especially relevant in socially-threatening situations such as ostracism. Alternatively, in agreement with most recent models on the development of emotion recognition abilities attributing distinct visual and neural processing in response to different emotions [ 37 39 , 51 , 52 ], it is also possible that the effects of ostracism may differ depending on the observed emotion. In line with the available literature, we expected age to modulate children’s ability to recognize emotions, with older children showing better emotion recognition performance than younger ones, but we presumed that in both age groups recognition of emotional expressions could be modulated by ostracism.…”
Section: Introductionsupporting
confidence: 81%
“…The current study aimed at investigating whether social ostracism modulates emotion recognition abilities in 5-and 10-year-old children, thus exploring whether this modulation varies across preschool-and school-aged children. A substantial number of studies demonstrated that early in life humans not only detect regularities and learn from predictable sequences of emotional faces [32,33], but also display an attentional bias and exhibit a complex neural network involved in the processing of facial emotional expressions [34][35][36][37][38][39]. However, substantial changes in the ability to recognize facial expressions of emotions occur between preschool and school ages.…”
Section: Introductionmentioning
confidence: 99%
“…At 7 months of age, an “adult-like neural circuitry” is engaged to process some emotional faces [sad and happy faces: Rotem-Kohavi et al (2017) ; fearful faces: Leppänen and Nelson (2009) ]. EEG studies have revealed that, as in adults, looking facial expressions elicits sensorimotor activity at 7 months of age, but only for happy faces ( Quadrelli et al, 2021 ). At this age, the brain response to happiness is different from negative expressions like angry faces for the temporal aspect (both right-lateralized), and the response to angry faces is associated with higher scores on a Negative Affect temperamental dimension ( Quadrelli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research into the processing of social signals in the first year of life (e.g., Bulf et al, 2015;Mermier et al, 2022;Quadrelli et al, 2019Quadrelli et al, , 2020Quadrelli et al, , 2021 as well as into early mother-infant interactions demonstrates that humans are sensitive to social signals from the first months of life (Mesman et al, 2009). Specifically, consistent evidence using the classical Face-to-Face-Still-Face (FFSF) paradigm shows that the sudden lack of maternal responsiveness elicits specific behavioral (i.e., increased negative affect and reduced smiling) and physiological (e.g., suppression of vagal tone) responses in the first year of life (e.g., Provenzi et al, 2016;Tronick, 2007).…”
mentioning
confidence: 99%